Sandoval, Rafico (2017). Economía extractivista en Colombia: Modelo minero energético destruyendo naturaleza y sociedad. Bogotá. Stilo Impresores Ltda. - Capera Figueroa, José Javier (Espacio Abierto, 2019)
.